Religion and Spirituality in Social Work Practice with Children and Adolescents: A Survey of Canadian Practitioners. - Kvarfordt, Connie L.; Herba, Kasha (Child & Adolescent Social Work Journal, 2018)
Empirical evidence about the relevance of religion/spirituality for children and adolescents contrasts with the limited number of studies inquiring about the role of religion/spirituality when working with this population. In response to this lack of knowledge, this study explored the professional attitudes, experiences, and practice behaviors of social workers and social service workers working with youth and determined the predictive factors for using spiritually-derived interventions. A cross-sectional survey design, with proportionate stratified sampling, was used to gather data from 307 Canadian social workers and social service workers working with youth in Ontario (response rate was 40%, with 5.06% margin of error). Respondents reported favorable views toward the role of religion/spirituality in social work practice, in general. They also reported positive attitudes about the relevancy of religion/spirituality for this population and somewhat frequent encounters with religious/spiritual abuse and neglect. They used a wide variety of spiritually-derived interventions; however, over two-thirds (69%) reported their formal education “never” or “rarely” included content on the topic. Barriers to using spiritually-derived interventions included: lack of knowledge/experience, concern about presenting one's own bias, disapproval from caregivers, and lack of agency/supervisor support. Multiple regression analysis revealed two assessment variables, two attitudinal variables, one education/training variable, and one personal religious/spiritual variable predictive of the use of spiritually-derived interventions, accounting for 55% of the variance. Findings suggest a need for emphasizing spiritually-sensitive practice guidelines and for social work education and continuing education to include content about religious/spiritual diversity as well as content about spiritual development that includes spirituality in childhood.